Postoperative complications in patients with rheumatoid arthritis using a biological agent – A systematic review and meta-analysis. Issue 5 (September 2015) - Ito, Hiromu; Kojima, Masayo; Nishida, Keiichiro; Matsushita, Isao; Kojima, Toshihisa; Nakayama, Takeo; Endo, Hirahito; Hirata, Shintaro; Kaneko, Yuko; Kawahito, Yutaka; Kishimoto, Mitsumasa; Seto, Yohei; et al.
Abstract Objectives. To evaluate, through a systematic review of the literature, the association between the use of biological disease-modifying antirheumatic drugs (bDMARDs) and surgical site infection (SSI) or wound healing delay after orthopedic surgery in patients with rheumatoid arthritis (RA). Methods. A systematic review of articles indexed in the Cochrane Library, PubMed, and Web of Science from 1992 to 2012 was performed. The search aimed to identify studies describing SSI or wound healing delay in patients with RA treated with or without bDMARDs. Articles fulfilling the predefined inclusion criteria were reviewed systematically and their quality was appraised. Results. There was no Cochrane review on this subject. We found 75 articles through specific searches of PubMed and Web of Science, and hand searching. After inclusion and exclusion by full-text review, 10 articles were found for SSI, and 5 articles for delayed wound healing. The use of bDMARDs appeared to increase the rate of SSI slightly, especially in large joint-replacement surgery. Delayed wound healing was not increased by the use of bDMARDs. However, the definitions of SSI and delayed wound healing varied between the reviewed articles. Most of the articles focused on tumor necrosis factor-α inhibitors. Conclusion. bDMARDs slightly increase the relative risk of SSI but not that of delayed wound healing after orthopedic surgery and should be used with appropriate caution.